7x-5=6x+(-4)

Simple and best practice solution for 7x-5=6x+(-4) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7x-5=6x+(-4) equation:


Simplifying
7x + -5 = 6x + (-4)

Reorder the terms:
-5 + 7x = 6x + (-4)
-5 + 7x = 6x + -4

Reorder the terms:
-5 + 7x = -4 + 6x

Solving
-5 + 7x = -4 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
-5 + 7x + -6x = -4 + 6x + -6x

Combine like terms: 7x + -6x = 1x
-5 + 1x = -4 + 6x + -6x

Combine like terms: 6x + -6x = 0
-5 + 1x = -4 + 0
-5 + 1x = -4

Add '5' to each side of the equation.
-5 + 5 + 1x = -4 + 5

Combine like terms: -5 + 5 = 0
0 + 1x = -4 + 5
1x = -4 + 5

Combine like terms: -4 + 5 = 1
1x = 1

Divide each side by '1'.
x = 1

Simplifying
x = 1

See similar equations:

| -21-6a+5a=3a-5a | | 5x-40=5x | | 10x=4x-57 | | 8-4x=2x-3-6x | | 4(6x-36)=72 | | 4x+5=25+2x | | 11x-2(3x-7)=19+2x | | (4x-1)=(2x+5) | | 30+5=51 | | -25x-6=-5(5x+7)+29 | | 10x+2+4x=(2+12)x-3+5 | | .25a-2=5 | | 12x-3(3x-6)=18+3x | | x-x(.25)=42000 | | 11(w+2)+14=2 | | 15b-2b=-9 | | 6x-30=7-2x | | 2x+3+6x-1=8x+2 | | -2(4+m)=10 | | 2x+3+6X-1=x+2 | | 27j-6=14j-7 | | 112=7w-168 | | 30m=22+80m | | 2x+24=-30+5x | | 21x+7=10x-1 | | 5(g-6)=48 | | 1.5x=1.23 | | r-9-(-42)=96 | | 9+4+10=56 | | 8(3x+40)=10 | | x^2-320=x-10 | | 3overx= |

Equations solver categories